Determining Factors of Career Commitment Moderated by Self-Efficacy among Generation Y in the Banking Sector Using Social Cognitive Theory (SCT) - Damayanti, Nur; Yahya, Khulida Kirana; Yean, Tan Fee; Maasir, Lidia; Abdullah, Tengku Mohd Khairal (APMBA (Asia Pacific Management and Business Application), 2022)
The banking industry's future will be filled by Generation Y or millennials, who differ from previous generations in their behavior and characteristics. This study explores banking leaders and managers in better understanding the work values of Generation Y employees. This study examined the role of self-efficacy in moderating the relationship between work values, emotional intelligence, and career commitment among employees in the banking sector in Jakarta, Indonesia using Bandura's Social Cognitive Theory. The survey method was used to collect data from 350 employees in the Indonesian banking industry. The Statistical Package for Social Science (SPSS) version 23.0 was used as the main statistical analysis. The statistical results reveal a significant positive relationship between work values and emotional intelligence with career commitment. For implications, management should reconsider their practices in order to determine the best way to attract, retain, and integrate Generation Y employees into the workforce. It also highlights the limitations. Firstly, the sample was restricted to Gen Y employees in the banking sector located in Jakarta. Secondly, this study was cross-sectional, and the findings provided a snapshot of the phenomenon in a specific period. Suggestions for future research are to examine the relationship of other variables and career commitments across companies and industries.